Structural relationship between the soluble and membrane-bound forms of human monocyte surface glycoprotein CD14 - Bazil, V; Baudys, M; Hilgert, I; Stefanová, I; Low, M G; Zbrozek, J; Horejsí, V (Molecular immunology, 1989)
The carboxy-terminal amino acid sequence of the soluble form of the 53,000 mol. wt monocyte surface antigen, CD14, was determined by carboxypeptidase Y digestion and compared with the complete amino acid sequence of this protein as predicted from the structure of cloned cDNA [Goyert et al. Science 239, 497-500 (1988)]. The soluble antigen isolated from urine appears to lack eight C-terminal amino acid residues predicted for the full-size translation product, but possesses a major part of the C-terminal hydrophobic domain originally suggested as the membrane-spanning segment. The CD14 antigen can be removed from the monocyte surface by phosphatidylinositol-specific phospholipase C treatment, indicating that this glycoprotein is anchored in the membrane by a phospholipid and is not a transmembrane protein. The soluble form occurring in serum and in supernatants of cultured monocytes thus probably arises by phospholipase-mediated cleaving off the cell surface antigen. A sensitive sandwich ELISA was developed using a monoclonal anti-CD14 antibody, MEM-18, and polyclonal rabbit anti-CD14 antiserum for quantitation of the soluble antigen concns in sera and cell culture supernatants. Using this assay, the antigen present in the supernatant of phospholipase treated peripheral blood mononuclear cells could be estimated. The assay was also used for estimation of the concns of the soluble form of the CD14 antigen in human sera.
Keywords: fosfolipasy typu C; antigeny povrchové; Electrophoresis, Polyacrylamide Gel; Type C Phospholipases; Humans; Amino Acid Sequence; lidé; Molecular Sequence Data; molekulární sekvence - údaje; Monocytes; Antigens, Surface; elektroforéza v polyakrylamidovém gelu; monocyty; Solubility; rozpustnost; sekvence aminokyselin